Media “HISTO-LADDER” Berbasis Gamifikasi untuk Meningkatkan Hasil Belajar Warisan Budaya Daerahku Siswa Kelas V SD - Ika Puspita Sari; Karimatus Saidah; Frans Aditia Wiguna (Lembaga Yasin AlSys, 2026)
Although the material on My Regional Cultural Heritage has an important role in strengthening students’ understanding of local cultural identity, the use of less varied instructional media still results in low student interest and active participation in the learning process. This study aims to develop gamification-based HISTO-LADDER instructional media for the My Regional Cultural Heritage material for fifth-grade elementary school students and to determine its level of validity, practicality, and effectiveness. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research participants consisted of media experts, material experts, fifth-grade teachers, and fifth-grade students of SD Negeri 1 Klagen. Data were collected through observation, interviews, questionnaires, and tests, and were then analyzed to determine the level of media validity, practicality, and effectiveness. The results showed that the HISTO-LADDER media obtained an average validity percentage of 86.85%, categorized as very valid, and an average practicality percentage of 86%, categorized as very practical. The effectiveness test results showed an improvement in students’ learning outcomes, as indicated by an increase in the mean pre-test score from 57.9 to 75.8 in the post-test and the results of the Paired Sample T-test with a significance value of 0.000 (<0.05). These findings indicate that gamification-based HISTO-LADDER media are feasible for use as innovative instructional media for the My Regional Cultural Heritage material. The conclusion of this study affirms that HISTO-LADDER media are very valid, very practical, and effective in improving students’ learning outcomes. The implications of this study provide alternative instructional media that are more engaging, interactive, and contextual for elementary school teachers in supporting local culture-based learning.